2013
DOI: 10.4236/msa.2013.48a010
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Agarose Mold as a Storage Container for Three-Dimensional Tissue-Engineered Cartilage

Abstract: The efficiency of substance exchange may be decreased when the thickness and volume of such a tissue-engineered cartilage that is composed of cultured cells and porous scaffold increase. Moreover, during the transport of this construct with complicated shapes, excessive and focal mechanical loading may cause deformation. The establishment of incubation and transport methods is necessary for the three-dimensional tissue-engineered cartilage. Therefore, we investigated the preparation of an agarose mold with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, it is difficult to compare hydrogel stiffness between studies because of confounders such as biomechanical loading and confinement, cross-linking methods and sample shape. Generally, hydrogel stiffness is concentration-dependent and power law-dependendent for agarose and gelMA [27,[36][37][38][39][40][41][42][43]. Of course at some point, polymer concentration will likely also inhibit matrix production through nutrient and oxygen deprivation, or changes in fixed charge density [44], although high concentrations of PEG (20% (w/w)) still enabled matrix production by bovine chondrocytes [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to compare hydrogel stiffness between studies because of confounders such as biomechanical loading and confinement, cross-linking methods and sample shape. Generally, hydrogel stiffness is concentration-dependent and power law-dependendent for agarose and gelMA [27,[36][37][38][39][40][41][42][43]. Of course at some point, polymer concentration will likely also inhibit matrix production through nutrient and oxygen deprivation, or changes in fixed charge density [44], although high concentrations of PEG (20% (w/w)) still enabled matrix production by bovine chondrocytes [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous reports, the sizes in pellets of mesenchymal stem cells and their analog, cultured chodrocytes, were usually confined within 1 mm, because larger pellets caused necrosis. The chondrocyte sheets of 3 mm square (10-100 μm of thickness) became a pellet of approximately 1 mm agarose mold was employed 15) . Agarose excels at substance permeability and the diffusion of water, nutrients, growth factors, and wastes.…”
Section: Discussionmentioning
confidence: 99%
“…Agarose molds were prepared according to the previous report 15) . Agarose (Takara Bio, Otsu, Japan) was mixed with MEM at 2% and dissolved at 121°C.…”
Section: Agarose Moldmentioning
confidence: 99%
“…We assumed that we can improve the efficiency of nutrition transfer using the agarose gel-supported well system. Agarose system is also easy to handle, has a low cost and a minimal biological effect on the cells and regenerative tissues [ 34 , 35 ]. The other advantage of using the agarose gels for the cell culture is that the nutrition or oxygen can freely diffuse through the agarose matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the agarose support could stably hold the assembly of the tissue-engineered constructs. Previously, it has been reported that 3-dimensional tissue-engineered cartilage generated in agarose mold has been used for clinical application [ 35 ].…”
Section: Discussionmentioning
confidence: 99%